Justice-oriented tourism education: Advocacy for reforming Global North curricula with Global South knowledge for sustainability - Acharya, Chet Narayan (Journal of International Students, 2025)
In an era calling for bold advocacy for radical transformations toward sustainability, Global North universities’ tourism curricula often overlook indigenous knowledge of the Global South, perpetuating unsustainable practices and exacerbating educational inequities. This study addresses the following question: How does justice-oriented tourism education integrate Global South perspectives to reform northern curricula for sustainability? Using a qualitative approach, the researcher conducted an ethnographic study with 7 indigenous individuals across the Global South and 12 Northern educators to assess impacts. The findings reveal that incorporating Global South perspectives, such as indigenous tourism models, enhances students’ cultural awareness and prepares them for sustainable tourism careers, although institutional resistance creates obstacles. This paper aims to advocate for justice-oriented curriculum reforms that empower Global South students, contributing to decolonial pedagogy and sustainable tourism education for inclusive and equitable global mobility.